Removal of Metal Ions From Ethanoic Acid Production Plant Waste Water Effluent, using Ion Exchange Resins and Activated Carbon - Krishna Moorthy, Utheswaran (Universiti Teknologi Petronas, 2009)
title of the final year project of the writer is ‘Removal of Metal Ions From Ethanoic Acid Production Plant Waste Water Effluent, using Ion Exchange Resins and Activated Carbon’. This report contains seven chapters, which are Introduction, Literature Review, Methodology, Results and Discussion, Conclusion, Recommendations and References. Appendix I is at the end of the report. The Introduction chapter explains about the problem statement and the objectives of the report. The main objective is to simultaneously remove the metal ions, which are Cr(3+), Fe(3+) and Ni(2+) from the industrial waste water using ion exchange resins and activated carbon. In the literature review chapter, explanations are given about the adsorption and ion exchange process which are the two main process applied for the metal ions removal. The type of ion exchange resin and adsorbents used are explained in this section. Next is the methodology part where the methods of the experiments done for this project are explained here. In the results and discussion part, the percentage of removal of the metal ions are tabulated and shown in graphs form. In the conclusion part, the best mixture of ion exchange resins and activated carbon that can produce maximum removal of metal ions from the waste water is concluded. From the experiment done, it was found out that the mixture of 30g Amberlyst 15 (Wet) resin + 10g Activated Carbon produces maximum amount of metal ions removal form the waste water sample. Finally is the reference part where source of information for this project to be done successfully are quoted.